Standardization of Terminalia myriocarpa Heurck and Muell. - Arg. - Arvind Dhabe, Priyanka Ingle* and (Journal of Phytology, 2011)
Terminalia myriocarpa Heurck and Muell. - Arg. synonym Myryobalanus myriocarpa is commonly known as Tolhao, Mezok in Manipuri, Panisaj in Bengali. It is a large evergreen tree. Its bark has medicinal value, it is diuretic, cardiac stimulant and antioxidant used in various drug preparations, which are sometimes adulterated with other plant materials. In order to standardize the drug, detail morphological, anatomical (Transverse section of bark, petiole and leaf; Transverse section, Transverse longitudinal section and Radial longitudinal section of wood and maceration of bark and wood) and dermatological studies were undertaken. It was observed that Terminalia myriocarpa Heurck and Muell.- Arg. can be easily standardized on the basis of combination of these parameters which are peculiar to this species. Key words: Standardization, Terminalia myriocarpa, Anatomy <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Priyanka Ingle and Arvind Dhabe. Standardization of Terminalia myriocarpa Heurck and Muell. - Arg. J Phytol 3/1 (2011) 09-12.